Measuring education inequality : Gini coefficients of education - Thomas, Vinod, 1949- 1949- (Policy research working paper, 2001)
Equal access to education is a basic human right. But in many countries gaps in education between various groups are staggering. An education Gini index -- a new indicator for the distribution of human capital and welfare -- facilitates comparison of education inequality across countries and over time